An overview on leveraging social media technology for uncovering tacit knowledge sharing in an organizational context - Amidi, Asra; Jusoh, Yusmadi Yah; Abdullah, Rusli; A. Jabar, Marzanah; Khalefa, Mustafa S. (IEEE, 2015)
Over the years, businesses have transformed from the traditional manufacturing-oriented to service-oriented. Along with this, tacit knowledge has become more crucial as organizations move toward innovation and service orientation. In summary, the knowledge of an organization's workforce is tacit knowledge related to their belief and expertise, which can be difficult to define, given its inexpressible characteristics. The practice of knowledge management is often associated with the use of information systems and the effort to codify, share and create knowledge using relevant knowledge management systems. Although social media is widely adopted by organizations to enhance the effectiveness of knowledge sharing practices, there is still a large amount of uncertainty on whether information systems act as an environment for the sharing of tacit knowledge. The purpose of this study is to understand the significant role of social media in offering tacit knowledge. Wiki, because of its collaborative and conversational bases, was chosen as an example of a social media and the methodology undertaken in this study is literature review. This study contributes to a discussion on the increasingly important role of social media in the dissemination of tacit knowledge in an organizational context.